SYSTEMATIC LITERATURE REVIEW: MEDIA PEMBELAJARAN GAME EDUKASI WORDWALL BERBASIS PMRI PADA SISWA - Rahmawati, Indah; Friansah, Drajat; Sukasno, Sukasno (LP4MK STKIP PGRI Lubuklinggau, 2024)
In this era, many children are actively playing online games, and teachers can use this as an aid in learning mathematics. Mathematics learning often uses context in everyday life through a real approach. This approach is known as Indonesian Realistic Mathematics Education (PMRI), where learning is carried out in a real-world context. A study was conducted to evaluate the use of PMRI-based word-wall educational games as a mathematics learning tool to increase students' understanding and interest in learning. The research method used was a Systematic Literature Review, which collected data from 2015 to 2024 by analyzing 29 articles from Google Scholar. The research results show that the use of PMRI-based Word-wall educational games can improve students' learning outcomes, motivation, understanding and interest in learning